Evaluation of rusinek-klapaczko model for high strain rate response of steel sheets - Syed Noh, Sharifah Nur’Ai Shikin (2013)
Automotive steel sheet structures are likely to experience high strain-rate loading during impact and crash conditions. A quasi-static stress-strain at low strain rate data alone may not give an accurate numerical prediction of sheet metal structure behaviour at high strain rates. In this study, the response of sheet metal which is low carbon steel with 0.045 C (wt %) and high strength steel, DP600 subjected to high strain rates loading is investigated. The Rusinek-Klapaczko (R-K) constitutive model is employed to predict the material behaviour at varying strain rates because the model incorporates strain, strain rates and temperature evaluation terms. In order to characterize the response of sheet metal at high strain rates, tensile experiments using an Instron machine were carried out at strain rates between 0.001 s-1 until 0.1 s-1 as a quasi-static rates and together with published high strain rate data up to the range of 500 s-1 was employed. These true stress-strain curves are used to extract the parameters of the R-K model. The R-K model predictive capability is then assessed by simulating a tensile test using finite element method (FEM). It was found that the R-K model is able to predict the tensile behaviour of the materials with an error of about 5 %. The validated R-K model was then incorporated into a FE simulation of bending of thin-walled tube made of low carbon steel and the results were compared with the experimental observation. It was found that the deformation of the structure has a good agreement with the experimental observation. The R-K model was also able to adequately capture the variation of the plastic strain rate in the structure